Disease-Based Prognostication: Myasthenia Gravis - Almodovar, Jorge L.; Mehrabyan, Anahit (Seminars in Neurology, 2023)
Myasthenia gravis (MG) is an acquired autoimmune neuromuscular junction transmission disorder that clinically presents as fluctuating or persistent weakness in various skeletal muscle groups. Neuroprognostication in MG begins with some basic observations on the natural history of the disease and known treatment outcomes. Our objective is to provide a framework that can assist a clinician who encounters the MG patient for the first time and attempts to prognosticate probable outcomes in individual patients. In this review article, we explore clinical type, age of onset, antibody status, severity of disease, thymus pathology, autoimmune, and other comorbidities as prognostic factors in MG.
Keywords: myasthenia gravis; prognostication; outcomes